On Modern Censorship in Public Service Broadcasting - Silber, Radomír (Cultural and religious studies, 2018)
The paper focuses on the manifestations, causes, and consequences of the failure of so-called public service media, especially in the field of news and journalism. Those media that, unlike private media, are funded from public sources. The public service, which citizens are obliged to pay through taxes or direct fees, is supposed to provide quality information, to produce and to disseminate content that satisfies the democratic, cultural, and social needs of the society, with a task at hand to preserve media pluralism. The major obligation of public service media is usually for them to provide objective, validated, and balanced information for people, so they can choose freely where they stand on any given issue. However, examples of the failures of two public service media operating in the Central European Czech Republic, Czech Radio (ČRo), and Czech Television (ČT), as well as the failures of the statutory control boards of these media, show that the required high quality public service prescribed by law, especially in the field of news and journalism and other programs, is not always kept. Public service media may be partisan and apply elements of modern censorship. This is a censorship that the law of the public service media does not impose and does not allow to carry out. Such censorship, which is a result of unilateral subordination of the influence of specific political parties, interest groups, and opinion streams, is reflected in information manipulation, purposeful agenda development, selection of information and information sources, spiral of silence, in the preference of some political parties, partisan, interest interpretation, and adaptation of reality in broadcasting.